Dietary Long-Chain Omega-3 Fatty Acids Are Related to Impulse Control and Anterior Cingulate Function in Adolescents - Darcey, Valerie L.; McQuaid, Goldie A.; Fishbein, Diana H.; VanMeter, John W. (Frontiers in Neuroscience, 2019)
Impulse control, an emergent function modulated by the prefrontal cortex (PFC), helps to dampen risky behaviors during adolescence. Influences on PFC maturation during this period may contribute to variations in impulse control. Availability of omega-3 fatty acids, an essential dietary nutrient integral to neuronal structure and function, may be one such influence. This study examined whether intake of energy-adjusted long-chain omega-3 fatty acids (eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA)) was related to variation in impulse control and PFC activity during performance of an inhibitory task in adolescents (n= 87; 51.7% female, mean age 13.3+1.1 years) enrolled in a longitudinal neuroimaging study. Intake of DHA+EPA was assessed using a food frequency questionnaire and adjusted for total energy intake. Inhibitory control was assessed using caregiver rating scale (BRIEF Inhibit subscale) and task performance (false alarm rate) on a Go/No-Go task performed during functional MRI. Reported intake of long-chain omega-3 was positively associated with caregiver ratings of adolescent ability to control impulses (p=0.017) and there was a trend for an association between intake and task-based impulse control (p=0.072). Furthermore, a regression of BOLD response within PFC during successful impulse control (Correct No-Go versus Incorrect No-Go) with energy-adjusted DHA+EPA intake revealed that adolescents reporting lower intakes display greater activation in the dorsal anterior cingulate, potentially suggestive of a possible lag in cortical development. The present results suggest that dietary omega-3 fatty acids are related to development of both impulse control and function of the dorsal anterior cingulate gyrus in normative adolescent development. Insufficiency of dietary omega-3 fatty acids during this developmental period may be a factor which hinders development of behavioral control.